1996
DOI: 10.1007/bf01712155
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate levels are better prognostic indicators than TNF and IL-6 levels in patients with septic shock

Abstract: These data indicate that the large variability in TNF alpha and IL-6 levels limit their prognostic significance in patients with septic shock. The predictive value of the trend in cytokine levels over time is not superior to that of trends in blood lactate levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 37 publications
3
28
0
2
Order By: Relevance
“…Esse resultado está em concordância com outros estudos que mostraram que dosagens únicas e precoces de lactato podem ser preditivas de mortalidade [11][12][13] . Alguns autores acreditam que a persistência de valores altos de lactato no curso da doença são mais sensíveis em predizer evolução desfavorável e morte 14,15 . Os resultados do presente estudo não encontraram correlação entre níveis de lactato e disfunção orgânica avaliada pelo escore SOFA.…”
Section: Métodounclassified
See 1 more Smart Citation
“…Esse resultado está em concordância com outros estudos que mostraram que dosagens únicas e precoces de lactato podem ser preditivas de mortalidade [11][12][13] . Alguns autores acreditam que a persistência de valores altos de lactato no curso da doença são mais sensíveis em predizer evolução desfavorável e morte 14,15 . Os resultados do presente estudo não encontraram correlação entre níveis de lactato e disfunção orgânica avaliada pelo escore SOFA.…”
Section: Métodounclassified
“…This is similar to the results of other studies demonstrating that the early determination of lactate levels can be predictive of the mortality [11][12][13] . Some authors believe that persistent, elevated levels of lactate during the evolution of the disease are more sensitive to predict unfavorable evolution and death 14,15 . The results of the present study did not demonstrate a correlation of lactate levels and organic dysfunction evaluated by the SOFA score.…”
mentioning
confidence: 99%
“…The functions of the lung parenchyma, measured by the p a O 2 , S a O 2 and p A-a O 2 parameters, did not change in both groups of animals monitored. Metabolic acidosis accompanies the development of SIRS and the analysis of blood gases and/or parameters of anaerobic metabolism, as confirmed by prior studies, may be suitable not only for the evaluation of the actual state of the patient but also for prognostic purposes (Smith et al, 2001;Marecaux et al, 1996). The increased anion gap values in the SS group at the end of the experiment correspond with the metabolic acidosis and the drop in the concentration of bicarbonates.…”
Section: Discussionmentioning
confidence: 59%
“…23,24 Marecaux et al showed that, when correlated with other markers, lactate has a better prognostic value than the tumor necrosis factor and IL-6. 25 Smith et al concluded that lactate can be used for the prognosis of outcome in (adult) ICU patients. 22 Besides these studies with adults, observations in pediatric patients for the establishment of laboratory parameters as predictors of death have presented controversial results.…”
Section: Discussionmentioning
confidence: 99%